SAT0590 AUTOMATED DIAGNOSIS EXTRACTION FROM ELECTRONIC MEDICAL RECORDS WITH MACHINE LEARNINGCLASSIFIERS. (June 2019) - Maarseveen, Tjardo; Huizinga, Thomas; Reinders, Marcel; Akker, Erik van den; Knevel, Rachel
Abstract : Background: While Electronic Medical Records (EMR) constitute a rich resource for research into various diseases, their unstructured format often poses practical challenges. For instance, retrieval of the records belonging to all patients with a particular outcome is often accomplished with naïve methods such as exact word matching. A more advanced alternative is to employ methods of Machine Learning (ML) for text classification. Rather than requiring a set of rules, an ML-model extracts these rules by itself given sufficient example records with known annotations. Objectives: To build a reliable classifier with machine learning techniques that can identify Rheumatoid Arthritis (RA) cases in provided EMR entries. Methods: Data was acquired from the HiX-EMR database consisting of 2, 771 patients that visited the rheumatology outpatient clinic of the Leiden University Medical Centre between 2007 and 2018. This database featured a total of 38, 216 entries. The first visit entry (if available) was selected per patient for annotation, resulting in a total of 1, 361 entries. The annotated sample was then randomly split into an equally sized training and test set. Both sets were preprocessed and then classified with the following methods: Exact word-matching, Naive Bayes (NB), Decision Tree, Gradient Boosting (GB), Neural Networks and Support Vector Machines (SVM), see table 1 for more information. Classification of the naïve word-matching model was based on the presence of the Dutch RA-defining terms 'Reumatoïde Artritis' and 'RA'. Default Scikit-learn implementations [1] were used to create the ML-models. Finally, the performance of the models was evaluated with a receiver operating characteristic (ROC) curve analysis via the pROC R-package [2]. The Delong test was used to assess the 95% confidence intervals (CI) and to determine the difference in performance between the word-matching method and the ML-models. Results: The exact word-matching approach resulted in an area under the curve (AUC) of 0.76 (CI: 0.7265-0.7783), see figure. Likewise, the ML-models resulted in relatively high AUC-scores (CI) as well: NB =0.83 (0.80-0.86), SVM=0.91 (0.89-0.93), Neural Networks=0.92 (0.90-0.94) and the GB-method with a 0.94 (0.92-0.96). The Decision Tree showed the worst performance with an AUC-ROC of only 0.51 (0.49-0.56). In comparison to the exact word-matching ROC-curve, all the ML-models showed a significant difference: Decision Tree (p<2.2e-16), NB (p= 0.004), Neural Networks (p<2.2e-16), GB (p<2.2e-16) and the SVM (p=4.0e-16). Conclusion: The Gradient Boosting, Neural Networks, SVM and Naïve Bayes models all showcased a significantly better performance than a naïve exact word matching, which establishes these ML-methods as an efficient approach for data extraction from EMR. References: [1] Pedregosa, F. et al. JMLR (2011) 12: 2825-2830 [2] Robin, X. et al. BMC Bioinformatics. (2011) 12: 77 Disclosure of Interests: Tjardo Maarseveen: None declared, Thomas Huizinga Consultant for: Merck, UCB, Bristol Myers Squibb, Biotest AG, Pfizer, GSK, Novartis, Roche, Sanofi-Aventis, Abbott, Crescendo Bioscience Inc., Nycomed, Boeringher, Takeda, Zydus, Epirus, Eli Lilly, Marcel Reinders: None declared, Erik van den Akker: None declared, Rachel Knevel: None declared